PYELONEPHRITIS ACUTE AND PREGNANCY - Siu, Alejandro (2015)
Objetive: To determine pyelonephritis incidence in pregnant women and to identify the most frequent microorganisms and their sensitivity to antibiotics. Design: Transversal, observational study. Setting. Arzobispo Loayza Hospital. Results: Pyelonephritis was present in 2,1 % of pregnant women, 58% occurred in the third trimester of gestation; all of them presented fever and pyuria, lumbalgia 92% and positive urine culture 79%; Escherichia coli grew in 87% of positive cultures. Most frequently used antibiotics as initial therapy were gentamycin (54%) and cephalotine (36%). Though, sensitivity was 100% for ceftriaxone, 96% for amikacine, 87% for nitrofurantoin, 83% for gentamycin and only 63% for cephalotine. Most frequent complications were both threatened abortion and threatened premature delivery, but there was only one abortion. Following treatment fever lasted 2 days and hospitalization 5 days. Conclusions: Incidence of pyelonephritis at Arzobispo Loayza Hospital is similar to other institutions and the most frequent microorganism cultured was Escherichia coli.